Sun protective behaviour of vacationers spending holidays in the tropics and subtropics. (1st October 2014) - Reinau, D.; Achermann, C.; Arnet, N.; Meier, C.R.; Hatz, C.; Surber, C.
Summary: Background: The development of malignant melanoma has been associated with intense episodic sun exposure, as it typically occurs during holidays in high ultraviolet (UV)‐index countries. Objectives: To investigate sun protective behaviour and sunburn experience of vacationers spending holidays in the tropics or subtropics. Methods: Using standardized face‐to‐face interviews, we conducted cross‐sectional surveys among air passengers waiting in the departure or the baggage claim area at the Airport Basel‐Mulhouse (Switzerland/France), and among vacationers waiting for pretravel health advice at a travel clinic in Basel (Switzerland). Results: We completed 533, 324 and 308 interviews with departing air passengers, returning air passengers and vacationers at the travel clinic, respectively. The interviews revealed widespread misconceptions about how to prepare the skin for the sun before holidays (e.g. pretanning in the solarium). At the holiday destination, almost all respondents used sunscreen, whereas wearing protective clothing and seeking shade were less practised. Among the returning air passengers, 44% had got sunburnt during their holiday stay. Conclusions: The sunburn rate among returning vacationers was alarmingly high. Skin cancer prevention campaigns and pretravel health advice should tackle misconceptions regarding the preparation of the skin for the sun, and emphasize the significance of covering up and seeking shade.